Chapter 10 The Anti-Fascist Cultural Theory of Nikolai Bukharin and the Concept of Socialist Humanism - Oittinen, Vesa (Taylor & Francis, 2023)
Nikolai Bukharin's (1888-1938) anti-fascist activity in the mid-1930s and his status as a cultural theoretician have been a neglected topic thus far. After losing his position as General Secretary of the Comintern's executive committee and being expelled from the Politburo in 1929, Bukharin still found a platform as the chief editor of Izvestiya, in which he published several analyses of fascist ideology until his arrest in 1937. As a response, and in order to surpass the achievements of German high culture, which had fallen under the spell of bourgeois fascism, Bukharin relied on his own interpretation of Marxist philosophy, which he had sketched already in the 1920s but tried to 'dialecticise' in the 1930s after being criticised for his overly mechanistic views. The apex of these aspirations are his works Philosophical Arabesques and Socialism and its Culture, written in 1937 while in prison. Both are in many respects rather enigmatic works. In them, Bukharin defended socialist humanism as the only real alternative to fascism. At the same time he was not only silent about the crimes of Stalin, but he also considered the violent and dictatorial features that became branded as Stalinism abroad as a necessary 'destructive' force in the dialectical process of history of building communism. In this chapter, Vesa Oittinen and Elina Viljanen analyse the premises of Bukharin's philosophy of culture and explain its repercussions.